Penerapan Aromaterapi Lavender Terhadap Penurunan Nyeri Pada Pasien Post Sectio Caesarea Di RSUD Kardinah Tegal - Nurinnisa Shiddiqiyah; Tin Utami (Pusat Riset dan Inovasi Nasional, 2023)
Sectio is a surgical operation to help pregnant women give birth by making an incision in the abdominal wall (laparotomy) and uterus (hysterectomy). Compared with regular births, which only cause about 9% more suffering, births by cesarean section cause about 27.3% more pain. Pharmacology and non-pharmacology can be used together to treat pain. Within 24 hours after a caesarean section, patients can experience a five times greater reduction in pain thanks to lavender aromatherapy. There are no risks associated with using the main active components of lavender oil, linalyl acetate, and linalool, which may provide a calming effect. When lavender aromatherapy is inhaled, the compounds it contains trigger the hypothalamus to produce endorphins which can calm and soothe. Lavender aromatherapy also has properties that make it antibacterial, analgesic, antidepressant and antispasmodic. By offering and using lavender aromatherapy, this research approach is descriptive and takes the form of a case report. The aim of this research is to determine whether the use of lavender aromatherapy can help patients after giving birth by caesarean section reduce their discomfort. After receiving lavender aromatherapy, the research findings changed from a scale of 7 to 3. Research findings show that the use of lavender aromatherapy can help postpartum patients undergoing cesarean section reduce their discomfort.